Cystatin C and estimated glomerular filtration rate as predictors for adverse outcome in patients with ST-elevation and non-ST-elevation acute coronary syndromes: results from the Platelet Inhibition and Patient Outcomes study - Åkerblom, Axel; Giannitsis, Evangelos; Katus, Hugo (Clinical chemistry, 2012)
BACKGROUND: We evaluated the predictive ability of cystatin C and creatinine-based estimations of glomerular filtration rate (eGFR), including the Chronic Kidney Disease-Epidemiology (CKD-EPI) equation, in acute coronary syndrome (ACS) patients with (STE-ACS) or without (NSTE-ACS) ST elevation in a large contemporary ACS population. METHODS: Concentrations of cystatin C and creatinine, as well as eGFR at randomization, were measured in 16 401 patients in the Platelet Inhibition and Patient Outcomes (PLATO) study and evaluated as predictors of the composite end point of cardiovascular death or myocardial infarction within 1 year. Two Cox proportional hazards models were used, the first adjusting for clinical characteristics and the second for clinical characteristics plus the biomarkers N-terminal pro-B-type natriuretic peptide, troponin I, and C-reactive protein. RESULTS: The median cystatin C value was 0.83 mg/L. Increasing quartiles of cystatin C were strongly associated with poor outcome (6.9%, 7.1%, 9.5%, and 16.2%). The fully adjusted hazard ratios per SD of cystatin C in the NSTE-ACS and STE-ACS populations were 1.12 (95% CI 1.04-1.20) (n=8053) and 1.06 (95% CI 0.97-1.17) (n=5278), respectively. There was no significant relationship of cystatin C with type of ACS (STE or NSTE). c Statistics ranged from 0.6923 (cystatin C) to 0.6941 (CKD-EPI). CONCLUSIONS: Cystatin C concentration contributes independently in predicting the risk of cardiovascular death or myocardial infarction in NSTE-ACS, with no interaction by type of ACS. CKD-EPI exhibited the largest predictive value of all renal markers. Nevertheless, the additive predictive value of cystatin C or creatinine-based eGFR measures in the unselected ACS patient is small.